The use of cold in the fruit and vegetable canning industry - Верхоланцева, Валентина Олександрівна; Верхоланцева, Валентина Александровна; Verkholantseva, Valentyna; Паляничка, Надія Олександрівна; Паляничка, Надежда Александровна; Palianychka, Nadiia (Oktan Print s.r.o., 2021)
In recent years, the functions of the refrigeration industry, which were previously reduced mainly to storage of products, have been supplemented by the organization of production of frozen products. High nutritional value allows them to be used for baby food, and the ability to produce a wide range of ready meals and semi-finished products creates conditions for improving the nutrition of the population through the catering system, promotes productivity in this area, is of great social importance because it facilitates household work. and increases the free time of employees. However, the production of quick -frozen products, low-temperature cooling and product freezing have not yet become widespread.
Keywords: storage of products; rapid freezing; freezing carrots; safety of vitam; vegetable industry